2017
DOI: 10.1039/c7ib00019g
|View full text |Cite
|
Sign up to set email alerts
|

Cellular orientation is guided by strain gradients

Abstract: The strain-induced reorientation response of cyclically stretched cells has been well characterized in uniform strain fields. In the present study, we comprehensively analyse the behaviour of human fibroblasts subjected to a highly non-uniform strain field within a polymethylsiloxane microdevice. Our results indicate that the strain gradient amplitude and direction regulate cell reorientation through a coordinated gradient avoidance response. We provide critical evidence that strain gradient is a key physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 69 publications
2
31
1
Order By: Relevance
“…In general, the complex microenvironment in which cells evolve in vivo gives rise to non-uniform, time-varying, anisotropic strain fields [21][22][23][24] . Importantly, in our previous work 16 , we have clearly demonstrated that cells have an ability to sense and respond to both strain and strain gradients. Yet, the large majority of previous cyclic stretching studies have focused on stretch patterns with nearly-uniform strain amplitude and direction [8][9][10][11]13,15 .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In general, the complex microenvironment in which cells evolve in vivo gives rise to non-uniform, time-varying, anisotropic strain fields [21][22][23][24] . Importantly, in our previous work 16 , we have clearly demonstrated that cells have an ability to sense and respond to both strain and strain gradients. Yet, the large majority of previous cyclic stretching studies have focused on stretch patterns with nearly-uniform strain amplitude and direction [8][9][10][11]13,15 .…”
Section: Introductionmentioning
confidence: 66%
“…Another example extensively studied to further our understanding of mechanotransduction processes is the cellular reorientation induced by cyclic stretching. More specifically, cyclically stretched cells were shown to exhibit elongation 7,8 , alignment perpendicular to the stretching direction [9][10][11][12][13][14][15] , and more recently fibroblasts were also demonstrated to exhibit strain gradient avoidance 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the complex microenvironment in which cells evolve in vivo gives rise to non-uniform, time-varying, anisotropic strain fields [21][22][23][24] . Importantly, in our previous work 16 , we have clearly demonstrated that cells have an ability to sense and respond to both strain and strain gradients. Yet, the large majority of previous cyclic stretching studies have focused on stretch patterns with nearly-uniform strain amplitude and direction [8][9][10][11]13,15 .…”
Section: Introductionmentioning
confidence: 66%
“…Another example extensively studied to further our understanding of mechanotransduction processes is the cellular reorientation induced by cyclic stretching. More specifically, cyclically stretched cells were shown to exhibit elongation 7,8 , alignment perpendicular to the stretching direction [9][10][11][12][13][14][15] , and more recently fibroblasts were also demonstrated to exhibit strain gradient avoidance 16 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In this paper we describe the fabrication steps of the MVAS, and to validate our approach, we characterize the bulk microtissue strain, the microtissue strain field and single cell strain, and assess changes in F-actin expression in response to chronic cyclic strain.…”
Section: Introductionmentioning
confidence: 99%